Seventh Five Year Plan 1985—90 Vol. I - Planning Commission (Planning Commission, 1985)
It is now almost four decades since we first embarked on the path of planned economic development. Over these years the planning process has grown in depth and sophistication and today it is an integral part of our national polity. It has helped to evolve a national consensus on how to pursue our basic objectives of removing poverty, building a strong and self-reliant economy and creating a social system based on equity and justice. The plan outlines our objectives and priorities for the next five years, within a longer term perspective of economic and social development. It embodies the collective aspirations of our people, as well as the commitment of Government to achieve specific goals and targets. The economy enters the Seventh Plan period in a strong position because of the success of the Sixth Plan. The rate of growth of GDP has accelerated over the past decade or so, and the Sixth Plan growth target of about 5 per cent has been achieved. Agricultural performance has been particularly impressive, specially in foodgrains. Steady growth in agriculture, reinforced by special schemes to help the weaker sections, has brought about a significant reduction in the percentage of the population below the poverty line. The rate of inflation has been kept under control and the balance of payments has been successfully managed despite an unfavourable external environment. These were years in which the world economy experienced the worst recession since the thirties and most developing countries, and even industrialised countries, faced severe economic difficulties. The Indian economy has emerged stronger. with an acceleration in growth.
Perspective, Objectives, Strategy, Macro-Dimensions and Resources